Increasing resource rent taxation when the corporate income tax is reduced? - Diderik Lund (University of Oslo, Department of Economics, 2018)
Under international tax competition, corporate income tax rates are predicted to decrease, and the tax burden will shift onto immobile factors. This case study considers tax changes that illustrate the predictions for Norway 2012-2018. Petroleum rent was taxed at high rates in 2012, and while corporate income tax rates were reduced in four steps, the marginal tax on rent was kept constant. The four steps are analyzed in light of the tax burden shift predicted by theory, and possible intentions of the government. The tax on petroleum rent has not been increased. Government intentions seem to have been shifting.
Keywords: H21; H25; H87; Q30; 330; rent taxation; tax competition; immobile factors; petroleum; Norway